Improvement of the antimicrobial activity of lactic acid bacteria in combination with berries/fruits and dairy industry by‐products. (20th March 2019) - Bartkiene, Elena; Lele, Vita; Sakiene, Vytaute; Zavistanaviciute, Paulina; Ruzauskas, Modestas; Bernatoniene, Jurga; Jakstas, Valdas; Viskelis, Pranas; Zadeike, Daiva; Juodeikiene, Grazina
Abstract: BACKGROUND: By‐products from berries/fruits (B/F) and the dairy industry (DI) are an important environmental issue in many countries. In the present study, the concept of an improvement of the antimicrobial activity of lactic acid bacteria (LAB) in combination with B/F (raspberries, blackcurrants, apples, rowanberries) and DI by‐products was analysed. Antimicrobial activities of the B/F by‐products and LAB (13 LAB strains were estimated against 15 pathogenic strains) were evaluated, with whey substrate being used for the selected and the highest antimicrobial activities showing LAB cultivation. RESULTS: The broadest spectrum of pathogenic bacteria inhibition was shown by lyophilised blackcurrant and apple by‐products, which inhibited 13 and 12 pathogenic strains of the 15 strains analysed, respectively. The strongest inhibition of the tested pathogens were shown by the Lactobacillus uvarum LUHS245 and Lactobacillus casei LUHS210 and, for the abovementioned LAB biomass preparation, whey enriched with 2.5 g 100 g −1 glucose, 2.0 g 100 g −1 yeast extract and 0.5 g 100 g −1 saccharose is a suitable and sustainable substrate. The B/F by‐product's antimicrobial activity can be enhanced in combination with the LUHS245 and LUHS210 strains. CONCLUSION: LAB, B/F and DI by‐products can be used for preparation of antimicrobial products because the combination of compounds from different origins showed higher antimicrobial properties. © 2019 Society of Chemical Industry